Znaczenie wybranych modeli w budowie organizacji uczących się - Adrianna Jednoralska (Studia i Materiały)
The article is a review of a literature on the topic of models of learning organizations. It presents and widely discusses the selected models and corresponding diagnostic tools of learning organizations. Three models and diagnostic tools of learning organizations of which Marsick and Watkins; Pedler, Burgogne, Boydell and Garvin, Gino and Edmondson are the authors were elaborated. As a result of this review, a comparison and an evaluation of the three was achieved. In addition, the similarities and differences between the three models and their ability and limits of use in the research on the learning organizations were stated. Moreover, pros and cons of each presented model and tool were identified and model’s and tool’s significance in the process of building a learning organization.